Personal Branding Jasa Penasehat Asuransi F1 Team Agency Bali - Ni Putu Yunita Anggreswari; I Gede Harry Ramanda Sujana (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the personal branding practices of insurance advisors at F1 Team Agency Bali in building public trust using Peter Montoya’s eight laws of personal branding framework. This research employs a qualitative descriptive approach with a case study method involving interviews, observations, and documentation. The findings reveal that all eight laws are implemented; however, the most dominant elements are the law of specialization, law of visibility, and law of personality. Specialization is reflected through consistent display of achievements and professional portfolios, visibility through continuous content dissemination on Instagram, and personality through authentic, relatable, and positive character presentation. These three elements significantly contribute to strengthening public trust and differentiating agents from competitors. The study highlights that effective personal branding in the insurance sector is not only about self-promotion but also about consistency, authenticity, and value-based communication in digital platforms.